Cooperative pathways for the green transformation of heavily polluting enterprises: A four-party game-driven mechanism for green M&A - Mengxin Sun; Xianggang Huang (PLoS ONE, 2025)
Amid the push for green transformation and industrial upgrades, how heavily polluting enterprises achieve green transition has become a focal point for the government and society. In response to policy demands, these enterprises often pursue green mergers as a means of transformation, though under varying conditions, they may opt for either green mergers or greenwashing, raising questions about their motivations. Based on evolutionary game theory, this paper constructs a four-party game model involving the media, government, public, and enterprises to analyze strategy stability. Using Lyapunov’s first law, this paper examine the stability of equilibrium points, investigating how factors like media transparency, regulatory strength, and public discernment affect corporate decisions. The findings show that: 1) corporate green mergers are significantly influenced by media authenticity, government oversight, and public discernment; 2) media and public supervision play crucial roles in curbing greenwashing. Based on these insights, we propose strengthening media supervision, optimizing regulatory policies, and enhancing public environmental awareness to promote green mergers.